PENGEMBANGAN PERTANIAN PADI ORGANIK BERBASIS DEVELOPMENT STRATEGY SEBAGAI UPAYA PENGUATAN PERTANIAN BERKELANJUTAN DI KABUPATEN KOLAKA - Hasbiadi, Hasbiadi; Masitah, Masitah (Fakultas Pertanian Universitas Mataram, 2023)
Organic farming is the answer to the impact of the green revolution being promoted at this time. Organic farming encourages producers and consumers of organic rice to increase productivity and food security. This relates to low input technology, environmental preservation, input/output efficiency, price accessibility and supports the Sustainable Development Goals (SDGs) to increase food security, sustainable consumption and production. The urgency of research was carried out to provide solutions to organic rice farmers in the form of recommendations related to steps and strategies for developing organic rice in Kolaka Regency. Research objectives to provide recommendations for organic rice development strategies. The analytical method includes a qualitative descriptive analysis arranged in the form of an IFE and EFE Matrix, SWOT and QSPM. The results of the study are that there are five development strategies including printing new rice fields and increasing organic rice production, packaging training, digital marketing and financial management, establishing partnerships with supporting stakeholders for organic farming, procuring Gasrok machines, chopping machines and repairing irrigation canals, improving quality and organic rice brand.